Study of job-related satisfaction: level of job satisfaction among teachers in Dehradun - Bharat Kumar (International Journal of Indian Psychȯlogy, 2022)
The objective of this study was to study the level of job satisfaction among post graduate teachers in different schools in Dehradun. The researcher used descriptive method involving measurement, evaluation, comparison, and interpretation. Total 360 PGTs, including equal number of males and females, were assessed. Dixit’s Job satisfaction scale (DJSS) was used to study the job satisfaction level. Mean, standard deviation and t-test were applied for statistical analysis of data and to find out significant difference. Level of job satisfaction among PGTs was found more toward average. 50.56% female PGTs are above the average category of job satisfaction as compared with 45.83 % male PGTs. It is observed that high numbers of PGTs are less satisfied (54.17 %). Female PGTs are more jobs satisfied as compared with male PGTs. The study reveals that 22.22 % PGTs enjoyed good level and 23.61 % PGTs enjoyed the highest level of satisfaction in their job. 54.17 % PGTs are under the average and below average level of satisfaction in their job. More males are at low level of job satisfaction (21.11%) as compared with 13.33% female PGTs. The result is significant and it can be helpful to design further education policies to improve teaching job quality.